Outreach initiatives to motivate Saparua residents in preserving the Perahu Belang heritage - Tri Ratna Purnamarini; Dody Wiranto (Universitas Muhammadiyah Magelang, 2024)
Community engagement plays a pivotal role in safeguarding cultural heritage from deterioration and loss. This community service program aimed to enhance the motivation of Saparua residents in preserving the Perahu Belang, a traditional boat. The program employed an outreach method, encompassing planning, implementation, and evaluation phases. The results demonstrated an increase in public awareness regarding the significance of Perahu Belang conservation as a cultural heritage and a surge in community motivation towards its preservation. It is hoped that this heightened knowledge and motivation will contribute to the enduring protection and preservation of the Perahu Belang legacy.